La Navidad y la Epifanía en las Tradiciones de Ricardo Palma - Coloma Porcari, César (2018)
Research work on Ricardo Palma’s description of the celebrations of Christmas and Epiphany, in colonial and nineteenth-century Peru. Nativity scenes, imagery, the dance of the “pallas”, male and female singers, Infant Jesus “urine”, the Epiphany, the Mayors Procession and the Epiphany in popular and lower class culture.